Plasticized polystyrene by addition of -diene based molecules for defect-less CVD graphene transfer - Nasir, Tuqeer; Kim, Bum Jun; Hassnain, Muhammad; Lee, Sang Hoon; Jeong, Byung Joo; Choi, Ik Jun; Kim, Youngho; Yu, Hak Ki; Choi, Jae Young (Polymers, 2020)
Chemical vapor deposition of graphene on transition metals is the most favored method to get large scale homogenous graphene films to date. However, this method involves a very critical step of transferring as grown graphene to desired substrates. A sacrificial polymer film is used to provide mechanical and structural support to graphene, as it is detached from underlying metal substrate, but, the residue and cracks of the polymer film after the transfer process affects the properties of the graphene. Herein, a simple mixture of polystyrene and low weight plasticizing molecules is reported as a suitable candidate to be used as polymer support layer for transfer of graphene synthesized by chemical vapor deposition (CVD). This combination primarily improves the flexibility of the polystyrene to prevent cracking during the transfer process. In addition, the polymer removal solvent can easily penetrate between the softener molecules, so that the polymer film can be easily dissolved after transfer of graphene, thereby leaving no residue. This facile method can be used freely for the large-scale transfer of 2D materials.
Keywords: Chemical vapor depositions (CVD); Critical steps; Metal substrate; Polymer removal; Polymer supports; Scale transfer; Structural support; Transfer process; Flexible polymer film; Graphene transfer; Polymer functionalization; Polymer plasticization; Polystyrene